Consistency management in multiple perspective medical decision analysis - Zheng J. (Institutional Knowledge at Singapore Management University, 1998)
Multiple perspective reasoning is often involved in real-world decision analysis. Different perspectives may be suitable for different stages of the decision modeling process. Multiple perspective modeling calls for consistency management which ensures that the different perspectives reflect the same information. This paper summarizes the graphical perspectives currently supported in DynaMoL, a new framework for dynamic decision analysis. We introduce a new perspective, the tree view, into the framework. We present the main ideas involved in consistency management in the framework. We also discuss the critical issues involved in multiple perspective modeling of a simplified case study in medicine. © 1998 IMIA. All rights reserved.